SELF REGULATORY-BASED WRITING: AN EFFECTIVE TECHNIQUE TO TEACH ARGUMENTATIVE ESSAY VIEWED FROM STUDENTS’ CREATIVITY - Samsul Arifin (English Teaching Journal : A Journal of English Literature, Language and Education, 2013)
The  objectives  of  the  research  are  to  identify  the  effectiveness  of  Self-Regulated Strategy Development to teach writing, and whether there is an interaction between the strategy and students’ creativity. This experimental study was conducted at one of the universities  in  Madiun.  The  population  was  the  third  semester  students  of  this university in the academic year of 2012/2013. Cluster random sampling was used to select  238  students  for  obtaining  two  classes  of  sample,  and  they  are  randomly classified into two groups: experimental and control group. The instruments of this research were writing test and creativity test. The data were analyzed using Liliefors and Bartlete tests to investigate the normality and homogeneity of the data, and ANOVA and  Tukey  to  test  the  hypothesis.  The  research  findings  show  that  self-regulated strategy development is more effective than collaborative writing to teach writing; the students having high creativity have better writing skill than those having low creativity; and there is an interaction between the strategy and students’ creativity in teaching writing. Thus, self-regulated strategy development  is an  effective  strategy to teach writing for students at university level. Therefore, it is better for lecturers to implement the strategy to accomodate students’ creativity.